2020
DOI: 10.7589/2019-10-262
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey for Pseudorabies (Aujeszky's Disease) in Free-Range Wild Boars (Sus scrofa) of Brazil

Abstract: Free-ranging wild boars ( Sus scrofa) from two different Brazilian biomes were sampled. Only one of 36 (0.03%) animals tested from central-western Brazil were positive for antibodies against pseudorabies virus (PRV) by enzyme-linked immunosorbent assay. Peccaries and other wildlife species can be exposed to PRV in these areas. In addition, wild boars could have impact on livestock and PRV eradication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, Aujeszky's disease has been reported in many other Brazilian states, such as Ceará, Mato Grosso do Sul, Santa Catarina, São Paulo, Rondônia, and, in 2018, in Paraná (BRASIL, 2021. In addition to cases in production pigs, several authors have reported Aujeszky's disease in wild pigs (CUNHA et al, 2006;PAES et al, 2013;CHIARI et al, 2015;KMETIUK et al, 2020). PAES et al (2013) reported a prevalence of 47.3% in free-living pigs in the Pantanal of Mato Grosso and identified viral latency and vertical transmission of the agent as important factors for epidemiology of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Aujeszky's disease has been reported in many other Brazilian states, such as Ceará, Mato Grosso do Sul, Santa Catarina, São Paulo, Rondônia, and, in 2018, in Paraná (BRASIL, 2021. In addition to cases in production pigs, several authors have reported Aujeszky's disease in wild pigs (CUNHA et al, 2006;PAES et al, 2013;CHIARI et al, 2015;KMETIUK et al, 2020). PAES et al (2013) reported a prevalence of 47.3% in free-living pigs in the Pantanal of Mato Grosso and identified viral latency and vertical transmission of the agent as important factors for epidemiology of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the Cerrado region of the state of Goiás, a positive serological diagnosis was made in a freeliving pig (1/36), suggesting the coexistence of SuHV1 circulation among the susceptible wild, production, and domestic animals (KMETIUK et al, 2020).The absence of cases in Espírito Santo excludes the need for vaccination of pigs against Aujeszky's disease, according to the Normative Instruction No. 8 (BRASIL, 2007), which allows the practice of vaccination only in properties with positive laboratory diagnosis under the control of the Official Veterinary Service.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, Aujeszky disease, caused by a herpes virus with major economic losses to swine industry worldwide, has been already isolated in wild boar tissues, indicating a role as disease amplifiers [ 44 ]. Out of a total of 94 free-ranging wild boars ( Sus scrofa ) from two different Brazilian biomes, 1/36 (0.03%) from central-western Brazil was seropositive for antibodies against pseudorabies virus (PRV), exposing livestock and free-range peccaries and other wildlife species in these areas [ 45 ]. In fact, an early study conducted in São Paulo state, southeastern Brazil with farmed wild boars before nationwide prohibition had already found an overall prevalence of 30.7% seropositive wild boars, which may have affected the Brazilian national pseudorabies eradication program [ 46 ] ( Table 2 ).…”
Section: Impact On Native and Livestock Animal Healthmentioning
confidence: 99%
“…Following successful prevention and eradication programs, PRV has been largely eliminated from domestic pigs in many parts of Europe, including Austria, Cyprus, Denmark, Finland, The Netherlands, and Great Britain (England, Scotland, and Wales) [ 41 ]. However, PRV infections remain widespread in many wild boar populations in the Czech Republic [ 44 ], Germany [ 41 , 45 ], France [ 46 ], Croatia [ 47 ], USA [ 48 , 49 , 50 ], Japan [ 51 ], Italy [ 16 , 52 , 53 ], Switzerland [ 52 ], Spain [ 53 , 54 ], Slovenia [ 55 ], Serbia [ 56 ], Brazil [ 57 ], Romania [ 58 ], Russia [ 59 ], Poland [ 60 ], and Belgium [ 61 ]. To date, however, there is little epidemiological information regarding PRV infection in Chinese wild boar populations.…”
Section: Prv Infection In Wild Domestic and Farm Animalsmentioning
confidence: 99%